South Korean Diaspora in Japan: Suffrage and Covid-19 Issues - Mauludino, Rizqi Wisnu; Iskandar, Kurniawaty (WILAYAH: The International Journal of East Asian Studies, 2022)
Ever since the conclusion of the Second World War, the Korean diaspora in Japan remains as one of the largest diaspora groups in the country even when compared to that of other nations. Currently, the majority of the diaspora are South Korean-affiliated, with their primary diaspora organization being the Mindan organization. This paper explains how Mindan, along with other South Korean-related organizations such as Seinenkai (Korean Youth Association) and Korean Chamber of Commerce in Japan (KCCJ), have taken actions to support the advocacy of the South Korean diaspora’s rights in the economic, cultural, politics, and many other fields. With varying levels of success, Mindan has become the most prominent Korean diaspora organization in Japan over the past few years as well as Seinenkai and KCCJ in advocating the living rights of the South Korean diaspora to create better living standards for their welfare in Japan.